Cidadania corporativa e imagem empresarial: um estudo de caso em uma empresa de telecomunicações em Uberlândia/MG - Mamede, Talita Tavares (2005)
The topic citizenship has been highly studied in the past few years, but few researches relate business social actions to a stronger corporative image. The purpose of this work is to identify how a company s social actions can strengthen its corporative image based on the studies of Maignan, Ferrell (2001) who show corporative citizenship according to legal, ethical, economic and philanthropic aspects in order to answer to stakeholders demands. The "Child Project" held by CTBC Company, which develops activities involving elementary school children and teachers, was analyzed. In this case study, the actions of the "Child Project" in a school of the town of Uberlândia MG, were examined from a research with parents, students and teachers. The results show that the people involved acknowledge CTBC as a citizen company.